Effects of Endotoxin in Cortisone-Treated Rabbits with a Hereditary Deficiency of the Sixth Component of Complement (C6 Deficiency) - Stafford, Benjamin T.; Rapaport, Samuel I.; Shen, Stephen M.-C. (Thrombosis and Haemostasis, 1976)
Endotoxin was infused into normal rabbits and C6 deficient rabbits prepared with cortisone for the generalized Shwartzman reaction. Endotoxin produced profound granulocytopenia and moderate thrombocytopenia in both normal and C6 deficient rabbits. In normal rabbits endotoxin consistently produced extensive intravascular clotting. In C6 deficient animals endotoxin resulted in intravascular clotting of variable extent. In one group of eight C6 deficient rabbits mean fibrinogen levels fell 0.67 g per 1 over 6 hrs after endotoxin and four of eight animals developed a generalized Shwartzman reaction. In a second group of seven C6 deficient rabbits mean fibrinogen level fell only 0.17 g per 1 over 6 hrs and one animal developed a generalized Shwartzman reaction. Values for mean fibrinogen consumption, calculated from plasma fibrinogen levels and rate of disappearance of 25I-fibrinogen, were as follows: normal animals infused with saline, 10 mg per kg; C6 deficient animals infused with endotoxin, 24 mg per kg; normal animals infused with endotoxin, 58 mg per kg. Fibrinogen consumption after endotoxin was found to be related to granulocyte levels prior to endotoxin, which determined the number of granulocytes disappearing from the blood after endotoxin. The data indicate that C6 deficiency in the rabbit does not prevent intravascular clotting and the generalized Shwartzman reaction.